Insufficient evidence to recommend routine adjunctive chest physiotherapy for adults with pneumonia. Issue 3 (3rd June 2010) - Agrafiotis, Michalis
Abstract : Commentary on: Yang M Yuping Y Yin X . Chest physiotherapy for pneumonia in adults . Cochrane Database Syst Rev 2010 ;2 :CD006338 .